2009
DOI: 10.1002/app.30383
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of ethylene‐vinyl alcohol copolymer treated with plasma source ion implantation

Abstract: The plasma source ion implantation technique was applied to modify the surface of ethylene-vinyl alcohol (EVOH) film using various working gases. The effects of the treated films were observed on the adhesion efficiency and physical properties. The hydrophobic properties of EVOH films were greatly enhanced after tetrafluoromethane-plasma source ion implantation (PSII) treatment. On the other hand, the higher hydrophilic properties of EVOH films increased after oxygen-PSII treatment. The results of X-ray photoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…Hong et al (2009) treated EVOH32 with plasma to modify the surface, which enhanced the hydrophobic properties due to the formation of fluorine-containing functional groups. [97] Tenn et al (2012) also used plasma treatment on EVOH29 and EVOH44 to generate hydrophobic surfaces. This reduced the P H 2 O up to 28% at 25 C. [98] Another study showed the use of hydrolysis reactions on an EVA copolymer film.…”
Section: Water Vapor Permeability Of Evohmentioning
confidence: 99%
“…Hong et al (2009) treated EVOH32 with plasma to modify the surface, which enhanced the hydrophobic properties due to the formation of fluorine-containing functional groups. [97] Tenn et al (2012) also used plasma treatment on EVOH29 and EVOH44 to generate hydrophobic surfaces. This reduced the P H 2 O up to 28% at 25 C. [98] Another study showed the use of hydrolysis reactions on an EVA copolymer film.…”
Section: Water Vapor Permeability Of Evohmentioning
confidence: 99%
“…Figure 6 shows the 13 CNMR spectra of EVOH before and after grafting. In 13 Brought to you by | University of Pittsburgh Authenticated Download Date | 6/3/15 5:28 AM 29.74 ppm, respectively. At the same time, new peaks at 27.31 and 31.17 ppm corresponding to NH-CH 2 -CH 2 -CH 2 and NH-CH 2 -CH 2 , respectively, of the nylon structure, appeared in the spectrum of the five pass sample.…”
Section: Hnmr and 13 Cnmr Investigationmentioning
confidence: 98%
“…Furthermore, EVOH copolymers with two different vinyl alcohol compositions have been modified to produce glycopolymers containing aminosaccharide pendant groups [12]. Surface treatment of EVOH with plasma source ion implantation was carried out by Hong et al [13]. Synthesis of sulfonated EVOH [14], EVOH-graftedpoly (3-hydroxybutyrate-co-hydroxyvalerate) copolymers [15], EVOH-graft-poly(ε-caprolactone) by reactive extrusion [16] and phosphorylcholine-modified poly(ethyleneco-vinyl alcohol) [17] has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…From the industrial standpoint, one of the more interesting surface treatments that can be used to improve the surface properties of the ionomer is treatment by atmospheric plasma. Polymers treated with this type of plasma have shown increased wettability, owing to the action of the plasma, which modifies surface functionality, thereby increasing surface energy (γ s ), providing the polymer with hydrophilic properties [10–14]. This effect is the result of the formation of free radicals over the surface of the treated ionomer; an interaction occurs between the ionomer chains and the ionized species created by the plasma current and from reactions with the air.…”
Section: Introductionmentioning
confidence: 99%